Preparation of acrylate‐based double and triple interpenetrating polymer networks hydrogels: Rheological, thermal, and swelling behavior. (17th September 2022) - Ghadami, Azam; Taheri, Somayeh; Alinejad, Zeinab; Dinari, Mohammad
Abstract: Two kinds of hydrogels based on acrylic acid (AA) and acrylamide (AAm) without and with 2‐acrylamido‐2‐methylpropane sulphonic acid (AMPS) were synthesized by radical polymerization using ethylene glycol dimethylacrylate as a crosslinker, to form double network (DN) and triple network (TN) interpenetrating polymer networks (IPN) gels, respectively. Fourier transform infrared spectroscopy (FTIR) presented evidence for the formation of polyacrylic acid (PAA)/polyacrylamide (PAAm) IPN gels and Michael‐type grafting of poly(AAm‐co‐AMPS) onto PAA in TN gels. The scanning electron microscopy micrograph images exhibited a microporous morphology for synthesized IPN gels which was more compact in TN hydrogel samples compared with DN hydrogels due to the presence of AMPS (which is also proved through energy dispersive X‐ray pattern and elemental analysis results) and higher crosslinking density in the structure of TN IPN hydrogels. Swelling behaviors indicated that TN superabsorbent gels presented 192.4 g/g water absorbency which was over three folds and 107 folds the swelling capacity of DN hydrogels and PAA in water, respectively. Additionally, TN alcogels showed enhanced swelling capacities of 99.1, 94.3, and 70.0 g/g in dimethyl sulfoxide, methanol and ethanol, respectively. The significant improvements in the values of absorbency related to TN gels compared to other samples can be attributed to the strong ionic sulfonic acid groups (SO3 H) in AMPS along with hydrogen bonding as a strong polyelectrolyte and the formation of a three‐component interpenetrating network structure with higher crosslink density. This structure formed in TN IPN gels can be responsible for elastic behavior, stable gel formation, and enhanced thermal stability of IPN hydrogels, as indicated by rheological, dynamic mechanical thermal analysis (DMTA), and thermogravimetric analysis (TGA) results.